Health literacy and the determinants of obesity: a population-based survey of sixth grade school children in Taiwan - Shu-Fang Shih; Chieh-Hsing Liu; Li-Ling Liao; Richard H. Osborne (BMC, 2016)
Abstract Background Health literacy has become an important health policy and health promotion agenda item in recent years. It had been seen as a means to reduce health disparities and a critical empowerment strategy to increase people's control over their health. So far, most of health literacy studies mainly focus on adults with few studies investigating associations between child health literacy and health status. This study aimed to investigate the association between health literacy and body weight in Taiwan's sixth grade school children. Methods Using a population-based survey, 162,209 sixth grade (11-12 years old) school children were assessed. The response rate at school level was 83 %, with 70 % of all students completing the survey. The Taiwan child health literacy assessment tool was applied and information on sex, ethnicity, self-reported health, and health behaviors were also collected. BMI was used to classify the children as underweight, normal, overweight, or obese. A multinomial logit model with robust estimation was used to explore associations between health literacy and the body weight with an adjustment for covariates. Results The sample consisted of 48.9 % girls, 3.8 % were indigenous and the mean BMI was 19.55 (SD = 3.93). About 6 % of children self-reported bad or very bad health. The mean child health literacy score was 24.03 (SD = 6.12, scale range from 0 to 32). The overall proportion of obese children was 15.2 %. Children in the highest health literacy quartile were less likely to be obese (12.4 %) compared with the lowest quartile (17.4 %). After controlling for gender, ethnicity, self-rated health, and health behaviors, children with higher health literacy were less likely to be obese (Relative Risk Ratio (RRR) = 0.94, p < 0.001) and underweight (RRR = 0.83, p < 0.001). Those who did not have regular physical activity, or had sugar-sweetened beverage intake (RRR > 1.10, p < 0.0001) were more likely to report being overweight or obese. Conclusions This study demonstrates strong links between health literacy and obesity, even after adjusting for key potential confounders, and provides new insights into potential intervention points in school education for obesity prevention. Systematic approaches to integrating a health literacy curriculum into schools may mitigate the growing burden of disease due to obesity.